Metody zarządzania przedsiębiorstwem rolniczym a efektywność działań rynkowych - Kiełkiewicz, Wioletta (Methods of Farms Management in the Affect of Efficiency Farmers Market Business, 2005)
The objective of the study was to analyse economic of different production types if farms and identification of factors which had the impact on farming efficiency. The study was permormed on a group of 290 farms in the Wrocław Region, representing two different types of farming: families farms - RGR (245 farms) and speciality production farms - DSPR (45 farms). Among the farm types investigated, RGR farms reached the lowest values of farm income and profitability ratios. The best economic results showed the farm group with DSPR. The analysis of that farms profitability was determined by the degree of specialization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 155-163